2002
DOI: 10.1097/00004850-200209000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Discontinuation symptoms: comparison of brief interruption in fluoxetine and paroxetine treatment

Abstract: Abrupt interruption or cessation of selective serotonin reuptake inhibitor (SSRI) treatment may result in discontinuation or treatment interruption symptoms. Recent reports suggested these symptoms occur more frequently with shorter half-life SSRIs. Previous studies indicated a 5-8-day treatment interruption resulted in fewer discontinuation-emergent adverse events in fluoxetine-treated patients than in paroxetine-treated patients. This study examines the effects of shorter treatment interruption (3-5 days), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
49
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(55 citation statements)
references
References 20 publications
5
49
1
Order By: Relevance
“…Such symptoms are highly character istic of primary discontinuation syndrome. The syndrome was initially reported in case reports and adverse drug reaction reports (Haddad, 1998) but its features have been confirmed in several doubleblind studies in which SSRI treatment is briefly interrupted with placebo (Rosenbaum et al, 1998;Michelson et al, 2000;Judge et al, 2002). A similar discontinuation syndrome occurs with venlafaxine (Fava et al, 1997) and duloxetine (Perahia et al, 2005).…”
Section: Primary Ssri Discontinuation Syndromementioning
confidence: 96%
See 1 more Smart Citation
“…Such symptoms are highly character istic of primary discontinuation syndrome. The syndrome was initially reported in case reports and adverse drug reaction reports (Haddad, 1998) but its features have been confirmed in several doubleblind studies in which SSRI treatment is briefly interrupted with placebo (Rosenbaum et al, 1998;Michelson et al, 2000;Judge et al, 2002). A similar discontinuation syndrome occurs with venlafaxine (Fava et al, 1997) and duloxetine (Perahia et al, 2005).…”
Section: Primary Ssri Discontinuation Syndromementioning
confidence: 96%
“…For example in a 6week doubleblind study that compared milnacipran with paroxetine both drugs were equally effective in treating depression, but after treatment discontinuation, paroxetine was associated with significantly more discontinuation symptoms (Vandel et al, 2004). Among the SSRIs several prospective studies have show that paroxetine is associated with the highest incidence of discontinuation symptoms and fluoxetine the lowest (Rosenbaum et al, 1998;Michelson et al, 2000;Bogetto et al, 2002;Judge et al, 2002;Tint et al, 2007).…”
Section: Incidencementioning
confidence: 99%
“…Agomelatine showed higher efficacy than paroxetine, a specific serotoninreuptake inhibitor, and both were effective in the treatment of anxiety symptoms in depression (Lôo et al, 2003). Agomelatine's profile of adverse effects, including discontinuation symptoms, is comparable with that of placebo and less than that of paroxetine (Judge et al, 2002;Lôo et al, 2003;Montgomery et al, 2004). Agomelatine seems to have an advantage over other current antidepressant treatments in that it promotes sleep Guilleminault, 2005), entrains circadian rhythms QueraSalva et al, 2005), and shows anxiolytic effects and a faster onset of therapeutic effectiveness (Lôo et al, 2002;Montgomery et al, 2004;Kennedy, 2005).…”
mentioning
confidence: 99%
“…Turning to newer antidepressants, Fava et al (1997) reported that during the three days following stoppage of venlafaxine and placebo under double blind conditions, seven (78%) of nine venlafaxine treated subjects and two (22%) of nine placebo-treated patients reported the emergence of adverse events, a statistically significant difference. Among the SSRIs prospective studies indicate that paroxetine is associated with the highest incidence of discontinuation symptoms and fluoxetine the lowest (Rosenbaum et al, 1998;Michelson et al, 2000;Judge et al, 2002;Bogetto et al, 2002;Tint et al, 2002). Several factors may account for this difference but the long half-life of fluoxetine and the existence of an active metabolite, norfluoxetine, with an even longer half-life seem important.…”
Section: Incidencementioning
confidence: 99%